Effects of composite alkaline activator on mechanical properties and hydration mechanism of cemented paste backfill with cement kiln dust - Minhui Hu; Tianwen Dong; Zhenglong Cui (Scientific Reports)
Abstract To address the low utilization rate and environmental pollution of mine tailings (MT) and cement kiln dust (CKD), a CKD-based cemented paste backfill (CPB) material was prepared using quicklime (CaO) and sulfate (DH-7) as a composite alkaline activator (CAA), with CKD and slag as the cementitious material and MT as the aggregate. The optimal dosage of the new CAA was determined through unconfined compressive strength (UCS) analysis. The reaction products, pore structure, and cation dissolution ability of CKD-based CPB activated by CAA were investigated, analyzing the mechanism of strength enhancement. The results showed that the CAA enhanced the compressive strength of CKD-based CPB by improving the reactivity of calcium hydroxide. The addition of the CAA led to elevated the dissolution concentration of cations such as Ca and Si within the system, accelerating both the alkali activation reaction rate and the nucleation rate of the calcium aluminosilicate hydrate (C–(A–)S–H) gel. Furthermore, with the increase in CAA content, the pore structure of CKD-based CPB became more complex. Therefore, this study may provide novel insights into the preparation of cost-effective CPB materials with a high CKD content.